Feminizacija za reprodukcijo kognitivnega kapitalizma - Pajnik, Mojca (Javnost (Ljubljana), 2017)
In the article, we analyse that the current situation of cognitive capitalism, which in the processes of media production introduce the temporary nature of work contracts, long working hours, the demand for unconditional commitment to work, etc., favors women's work. We verify the thesis that the increased number of women in the media industry corresponds to the profitable orientation of modern cognitive capitalism and to the imagination of the work that it presumes, thereby reproducing gender inequalities. Attention is paid to demitologising work in the media as "de-gendered" work with the analysis of feminisation and the increase in individualisation in the media, the rise of "entrepreneurial subjectivity" characterised by denial of inequality, and precarisation of production processes and the related devaluation of journalism as a profession. The analysis of so called "de-gendered engendering" of the media is based on 21 interviews conducted with journalists on three televisions in Slovenia, public TV SLO and commercial POP TV and Planet TV.
Keywords: delovne pogodbe; delovni pogoji; feminizacija; kapitalizem; množični mediji; neenakost; novinarji; novinarstvo; ugled